PRODUCTIVITY AND QUALITY OF WHEAT AS INFLUENCED BY TILLAGE, RESIDUE AND NITROGEN MANAGEMENT UNDER RICE-WHEAT CROPPING SYSTEM - KUMAR, SANDEEP; PANDEY, D.S.; RANA, N.S.; KUMAR, SANJAY; SINGH, OMBIR (Annals of Agricultural Research, 2014)
Twenty one treatment combinations comprising of seven tillage types clubbed with rice residue management practices and three nitrogen management schedules were evaluated at Crop Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar, for devising suitable tillage and nitrogen management practice for getting sustained productivity and quality of wheat crop under rice-wheat system. They study substantiated that the higher grain as well as protein yield of wheat could be otained by deep incorporation of rice residue either by disc plough or mould-board plough. Retention of residue in field modified the micro-climate suited for crop growth as indicated by canopy temperature depression. Grain growth rate were higher from the residue retention with conservation tillage. (zero and strip). The higher net return was obsurved by burying the rice residues deep. The available soil nitrogen increased by the incorporation/retention of residue irrespective of tillage type. The uptke of nitrogen by the crop followed the same pattern of grain yield. The application of starter dose of 20 kg N/ha at the time of field preparation could be saved by applying 2/3 of recommended dose of nitrogen at basal and rest 1/3 at CRI.